Using questions, dialogue and discussion to facilitate and explore students learning - Vlasenko, Ludmila; Trygub, Inna (My University, 2011)
This article introduces a technique for designing a course which utilizes questions, dialogue and discussion to facilitate and explore students learning The article gives some background into theory behind content-based learning.
Keywords: запитання та обговорення; спілкування іноземною мовою; навички; социокультурные темы; обсуждения на английском; навыки; sociocultural issues; discussions in English; skills; кафедра ділової іноземної мови та міжнародної комунікації